Enhancing Revisit Intention To Jember Fashion Carnaval: The Role Of Celebrity Endorsement, Event Image, And Visitor Attitude - Paramita, Cempaka; Wulandari, Gusti Ayu; Salsabila, Raissa Aulia (Jurnal Mebis, 2025)
The Jember Fashion Carnaval (JFC) is one of the most important international cultural events in Jember and has been attracting increasing numbers of visitors. However, the challenge lies not only in attracting new visitors but also in encouraging them to return. Therefore, this study explores celebrity endorsement and event image effect to revisit intention of JFC and the mediating role of visitor attitude from survey data results of 160 respondents who filled the questionnaire about the variables measurement on JFC. The data analysis was performed using SmartPLS 4. Findings from this research reveal that event image and visitor attitude significantly affect revisit intention to JFC in a positive direction. This study also proves that celebrity endorsement and event image through the mediation of visitor attitudes can positively influence revisit intentions. However, it is noteworthy that celebrity endorsement does not affect visitors’ intention to revisit directly.